Advanced Management Protocol of Transanal Irrigation in Order to Improve the Outcome of Pediatric Patients with Fecal Incontinence - Anna Maria Caruso; Mario Pietro Marcello Milazzo; Denisia Bommarito; Vincenza Girgenti; Glenda Amato; Giuseppe Paviglianiti; Alessandra Casuccio; Pieralba Catalano; Marcello Cimador; Maria Rita Di Pace (MDPI AG, 2021)
Background: Transanal irrigation (TAI) is employed for children with fecal incontinence, but it can present several problems which require a study of their outcomes among different pathologies and without a tailored work up. The aim of our study was to evaluate the effectiveness of an advanced protocol in order to tailor TAI, prevent complications, and evaluate outcomes. Methods: We included 70 patients (14 anorectal malformation, 12 Hirschsprung's disease, 24 neurological impairment, 20 functional incontinence) submitted to a comprehensive protocol with Peristeen®: fecal score, volumetric enema, rectal ultrasound, anorectal 3D manometry, and diary for testing and parameter adjustment. Results: Among the patients, 62.9% needed adaptations to the parameters, mainly volume of irrigated water and number of puffs of balloon. These adaptations were positively correlated with pre-treatment manometric and enema data. In each group, the improvement of score was statistically significant in all cases (p 0.000); the main factor influencing the efficacy was the rate of sphincter anomalies. The ARM group had slower improvement than other groups, whereas functional patients had the best response. Conclusions: Our results showed that TAI should not be standardized for all patients, because each one has different peculiarities; evaluation of patients before TAI with rectal ultrasound, enema, and manometry allowed us to tailor the treatment, highlighting different outcomes among various pathologies, thus improving the efficacy.